Nanotechnology as general purpose technology - Florian Kreuchauff; Nina Teichert (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2014)
Scientific literature postulates that nanotechnology is to be considered as general purpose technology (GPT), characterized by pervasiveness, high technological dynamism and the inducement of innovations within a variety of applications. We set out to not only further systematize existing approaches investigating nanotechnology's GPT traits based on patent applications, but to extend the analysis to academic publication data, in order to cover both knowledge creation and application development. By utilizing well established and consolidated indicators of GPT features, such as generality, diffusion, and forward citation rates, as well as contextualized technological coherence as a new weighted generality measure, we compare nanotechnology's research output to the ones of ICT as accepted GPT and of the combustion engine as a non- GPT, representing an upper and lower benchmark, respectively. Moreover, we add the EU27 as new institutional setting. Our results indicate that while nanotechnology is not as clearly perceptible a GPT as ICT is, the potential to develop as such and hence to become an 'engine of growth' is clearly given.
urn:nbn:de:swb:90-378284
Keywords: O33; O30; O34; 330; general purpose technology; nanotechnology; patents; publications; generality; technological coherence